Study on the Diversity and Potential of Fisheries Resources in the Waters of Bone Regency, South Sulawesi. - Muhammad Gazali; Neneng Rahayu Ningsih; Hikmah Maulifia Zaim; Muhammad Rijal Kasim; Muhammad Afif Bahda (Jurnal Studi Perikanan Berkelanjutan, 2025)
Bone Regency is one of the coastal areas in South Sulawesi with abundant fisheries resources, both in marine and freshwater environments. This study aims to analyze fish species diversity, catch potential, and environmental factors influencing fisheries sustainability in the waters of Bone Regency. Data were collected through field surveys, fisher interviews, and environmental parameter measurements such as temperature, salinity, and water pH. The research was conducted from March to May 2025 at several water sites, including the coastal area of Bone Bay, the Walanae River, and several community aquaculture ponds. The results showed that more than 25 dominant fish species were caught by fishers, with major contributions from small pelagic fish (sardinella, anchovy), demersal fish (grouper, snapper), and freshwater species (tilapia, milkfish). Data analysis revealed a moderate to high species diversity, with Shannon-Wiener index (H’) values ranging from 2.5 to 3.2. Environmental factors played an important role in determining fish availability, particularly during the transitional season. Fishers’ catches showed a declining trend compared to the past five years, presumably due to overfishing pressure and habitat degradation. These findings highlight the need for ecosystem-based fisheries management and the adoption of environmentally friendly fishing gear. Education and fisher assistance programs are highly recommended to ensure the sustainability of fisheries resources in Bone Regency.